Efektivitas Iklan di Radar TV Lampung oleh PT. Marionsam Terhadap Keputusan Membeli Konsumen - Puspitasari, Dewi; Sari, Novita (Universitas Islam Kadiri, 2025)
This research aims to analyze the effectiveness of advertisements broadcast on Radar TV Lampung by PT. Marionsam on consumer purchasing decisions. In the digital era, marketing through advertising has become very important, especially for Small, Micro and Medium Enterprises (MSMEs) who have to compete with local and imported products. The method used in this research is a quantitative method, using a questionnaire, the data management tool in this research uses SPSS. The research results show that effective advertising can increase consumer buying interest, with an average purchasing decision value reaching 10.67 and a standard deviation of 2.83. In addition, online advertising and media variables also show a significant contribution to purchasing decisions, with average values of 10.48 and 8.83 respectively. This research confirms that the right advertising strategy can increase consumer satisfaction and encourage purchasing decisions. The conclusion of this research is the importance of utilizing technology and digital platforms as well as TV advertising in marketing strategies to reach a wider market.